2023
DOI: 10.1007/s10238-023-01125-x
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 cytokines and scleroderma interstitial lung disease

Abstract: Interstitial lung disease (ILD) is a life-threatening complication of systemic sclerosis (SSc). Type 2 (Th2) cytokines play a pivotal role in airway disease. Study aim was to evaluate serum level of Th2 interleukin (IL) and chemokine in SSc-ILD. Serum levels of IL-4, IL-5, IL-11, IL-13, IL-21, IL-31 and CXCL-13 were measured by Bio-Plex Multiplex Immunoassays in 60 SSc patients and 20 healthy controls (HC). Pulmonary function tests with diffusion lung capacity for carbon monoxide (DLco) and high resolution com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The SSc vascular damage is characterized by the presence of a characteristic processes with a vasomotor instability with an imbalance of vasoactive factors: overproduction of vasoconstrictors (ET-1) and underproduction of vasodilators (NO and prostacyclin) [6][7][8][9][10][11][12][13][22][23][24][25][106][107][108][109]. The free radical nitric oxide (NO) is a potent vasodilator and is synthesized from L-arginine by NO synthase (NOS) [10][11][12][13][14][15][16][17][18][19][22][23][24][25][40][41][42][43][44][45][46][47][48][106][107][108][109][110][111][112][113]. Endothelial isoforms of NOS (eNOS or NOS 3) has been identified with a constitutive expression, other isoforms are shown...…”
Section: The Role Of Endothelial Injury In Systemic Sclerosis Pathoge...mentioning
confidence: 99%
See 4 more Smart Citations
“…The SSc vascular damage is characterized by the presence of a characteristic processes with a vasomotor instability with an imbalance of vasoactive factors: overproduction of vasoconstrictors (ET-1) and underproduction of vasodilators (NO and prostacyclin) [6][7][8][9][10][11][12][13][22][23][24][25][106][107][108][109]. The free radical nitric oxide (NO) is a potent vasodilator and is synthesized from L-arginine by NO synthase (NOS) [10][11][12][13][14][15][16][17][18][19][22][23][24][25][40][41][42][43][44][45][46][47][48][106][107][108][109][110][111][112][113]. Endothelial isoforms of NOS (eNOS or NOS 3) has been identified with a constitutive expression, other isoforms are shown...…”
Section: The Role Of Endothelial Injury In Systemic Sclerosis Pathoge...mentioning
confidence: 99%
“…Endothelial isoforms of NOS (eNOS or NOS 3) has been identified with a constitutive expression, other isoforms are shown in other cell types. Furthermore, an inducible expression (iNOS or NOS 2) in response to a variety of stimuli is possible, with NO-mediated signalling apparent in the skin [10][11][12][13][14][15][16][17][18][19][40][41][42][43][44][45][46][47][48][106][107][108][109][110][111][112][113]. Several studies reported that NO have a biphasic effect in physiological and pathological conditions, being both beneficial and detrimental depending on the concentration and local environment [10][11][12][13][14][15][16][17][18][19][40][41][42][43][44][45][46][47][48].…”
Section: The Role Of Endothelial Injury In Systemic Sclerosis Pathoge...mentioning
confidence: 99%
See 3 more Smart Citations